PENGARUH BREATHING RELAXATION DENGAN TEKNIK BALLOON BLOWING TERHADAP SATURASI OKSIGEN PADA ANAK DENGAN ASMA - Sherly Widianti; Elly (LPPM STIKes Mitra Adiguna, 2026)
Asthma is a chronic respiratory disease commonly found in children and may cause ventilation disorders and decreased oxygen saturation, especially during asthma attacks. Unmanaged decreases in oxygen saturation can affect clinical conditions and quality of life. Asthma management is not only pharmacological but can also be combined with non-pharmacological interventions, such as breathing relaxation using the balloon blowing technique. This study aimed to determine the effect of breathing relaxation with the balloon blowing technique on oxygen saturation in children with asthma in the working area of Puskesmas Sosial Palembang in 2025. This quantitative study used a pre-experimental one group pretest–posttest design. The sample consisted of 31 children with asthma selected based on inclusion and exclusion criteria. Oxygen saturation was measured using a pulse oximeter before and after the intervention. Data were analyzed using the Wilcoxon test. The results showed that the median oxygen saturation increased from 95% before the intervention to 98% after the intervention. The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of breathing relaxation with the balloon blowing technique on oxygen saturation improvement. It can be concluded that the balloon blowing technique is effective in increasing oxygen saturation in children with asthma.